Asymptotic MIMO Channel Model for Diffusive MC With Fully-Absorbing Receivers - Vakilipoor Takaloo, Fardad; Ferrari, Marco; Magarini, Maurizio (IEEE Wireless Communications Letters, 2022)
This letter introduces an analytical model that gives the expected asymptotic cumulative number of molecules absorbed by each spherical receiver in a diffusive multiple-input multiple-output (MIMO) molecular communication (MC) system with pointwise transmitters. The reciprocal effect among the fully absorbing (FA) receivers is taken into account by using the recently introduced concept of fictitious pointwise negative source of molecules. An agreement is shown between the proposed asymptotic model and the numerical solution of the exact analytical one from the literature describing the interaction among the receivers, which is computed for a sufficient long time.
Created from Fastlane, Scopus look-up
Keywords: Asymptotic analysis; Diffusive MIMO channels; Fully absorbing receiver; Molecular communication